Using Video as A Learning Media in Class During the Covid-19 Pandemic - Asmarita; Pramoda Patro; Miressa Amenu Terfa (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
Based on the current situation during the COVID-19 pandemic, as well as regulations made by the government to conduct online learning processes, SDN 34 Kinali follows the circulating rules by studying online to help reduce the transmission of COVID-19 that is being faced. So to continue to carry out the learning process, media is needed in conveying material to students, learning media is a tool used to convey material messages to students that stimulate students' minds and attract students' interest in carrying out learning in order to achieve the expected goals in learning. In this study, the purpose of this study was to use an application for editing learning videos at SDN 34 Kinali Pasaman Barat in class V theme 6 sub-theme 1, in making videos in the Kinemaster application, namely by using various features in order to attract students' interest in listening to lessons during the pandemic. Faced at this time. In the current condition, learning videos are very much used so as not to make students lazy in participating in learning that is carried out if only through wa only. Therefore, the kinemaster used in video editing is a good electronic tool and easy to apply.